Repeatability and Reproducibility of Intraocular Pressure and Dynamic Corneal Response Parameters Assessed by the Corvis ST - Bernardo T. Lopes; Cynthia J. Roberts; Ahmed Elsheikh; Riccardo Vinciguerra; Paolo Vinciguerra; Sven Reisdorf; Stefanie Berger; Robert Koprowski; Renato Ambrósio (Journal of Ophthalmology)
Purpose. To assess the repeatability and reproducibility of dynamic corneal response parameters measured by the Corvis ST (Oculus, Wetzlar, Germany). Methods. One eye randomly selected from 32 healthy volunteers was examined by the Corvis ST. Three different devices were used in an alternated random order for taking three measurements at each device in each subject. Standard intraocular pressure (IOP), the biomechanical-compensated IOP (bIOP), and DCR parameters were evaluated. The within-subject standard deviation (ζw) and coefficient of variation (CV) were assessed. Results. Regarding pressure indices, the ζw was below 1 mmHg for repeatability (0.98 for IOP and 0.89 for bIOP) and the CV was 6.6% for IOP and 6.1% for bIOP. For reproducibility, the ζw was around 1 mmHg (1.12 for IOP and 1.05 for bIOP) and the CV was 7.6% for IOP and 7.1% for bIOP. Most of DCR indices presented CV for repeatability below 4%. For reproducibility, the CV of most of the indices were below 6%. The deformation amplitude (DA) ratio in 1 mm and integrated radius were below 4% (1.2% and 3.8%, resp.). Conclusions. The Corvis ST showed good precision (repeatability and reproducibility) for IOP measurements and for DCR in healthy eyes.